2015
DOI: 10.1097/md.0000000000000620
|View full text |Cite
|
Sign up to set email alerts
|

Necessity of Harvesting At Least 25 Lymph Nodes in Patients With Stage N2–N3 Resectable Gastric Cancer

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 18 publications
2
27
0
Order By: Relevance
“…Chen et al [19] reported that the mean number of lymph nodes retrieved by D1, D11, and D2 lymphadenectomy was 17, 21, and 28, respectively. Using 25 lymph nodes as the cutoff value, survival benefits were observed in patients with N2 and N3 gastric cancer in the LN >25 group compared with those in the LN <25 group.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Chen et al [19] reported that the mean number of lymph nodes retrieved by D1, D11, and D2 lymphadenectomy was 17, 21, and 28, respectively. Using 25 lymph nodes as the cutoff value, survival benefits were observed in patients with N2 and N3 gastric cancer in the LN >25 group compared with those in the LN <25 group.…”
Section: Discussionmentioning
confidence: 99%
“…The surgical specimens and lymph nodes were examined by pathologists specializing in gastric cancer using the updated edition of the UICC/ AJCC TNM staging system, which was then converted to the seventh edition at the time of our analysis [9]. For the purposes of the present study, the patients were divided into three groups according to the number of lymph nodes retrieved: patients with 15 harvested lymph nodes (LN 15), patients with 16-25 harvested lymph nodes (LN [16][17][18][19][20][21][22][23][24][25], and patients with >25 harvested lymph nodes (LN >25). The lymph node ratio (LNR) was defined as the ratio between metastatic and examined lymph nodes.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A one-way ANOVA and Pearson c 2 test were used for the univariate analyses where appropriate. The survival analysis was performed as previously reported (16). The KaplanMeier method was used to calculate the survival rates.…”
Section: Discussionmentioning
confidence: 99%
“…Studies suggest that removal and examination of more than 16 nodes might improve survival and increases the accuracy of staging by reducing understaging, which leads to stage migration 14,15 .…”
Section: Qualifying Statements For Recommendationmentioning
confidence: 99%